2016
DOI: 10.1097/icl.0000000000000173
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Outcomes of Kocuria Keratitis

Abstract: Bacterial keratitis by Kocuria spp. is a rare infection that may have an unexpected clinical course and possible serious outcomes. This pathogen should be considered in patients with unusual clinical course. Local or systemic immune compromise in the genesis of the disease must also be taken into account, and ophthalmologists should be more suspicious in this vulnerable group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
4
0
3
Order By: Relevance
“…In a retrospective study from China describing the causative organisms in infectious endophthalmitis, 1/330 cases reported was reported as Kocuria [ 17 ]. While cases of Kocuria keratitis have been reported previously with variable visual outcome [ 18 , 19 ], this is the first detailed description of endophthalmitis caused by Kocuria sp. Kocuria is a member of the Micrococcaceae family and currently includes 18 species [ 1 , 2 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study from China describing the causative organisms in infectious endophthalmitis, 1/330 cases reported was reported as Kocuria [ 17 ]. While cases of Kocuria keratitis have been reported previously with variable visual outcome [ 18 , 19 ], this is the first detailed description of endophthalmitis caused by Kocuria sp. Kocuria is a member of the Micrococcaceae family and currently includes 18 species [ 1 , 2 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that these species are related to skin diseases such as dermatitis ( 41 , 42 ), where over-colonization of these microbial species has been found, especially in areas where there are numerous sebaceous glands (as occurs in the eyelids) ( 43 ). Within the allergic groups, a considerable number of subjects reported having suffered from dermatitis at some point in their lives, so it is not unreasonable to think that they continued to have active skin disorders or blepharitis, making the ocular surface an appropriate place for the expansion of these species.…”
Section: Discussionmentioning
confidence: 99%
“…Kocuria spp. are also unusual causative organisms in ocular infectious diseases, and there are a small number of reports on Kocuria keratitis [5, 6]. …”
Section: Introductionmentioning
confidence: 99%